Linear control of wireless charging for electric bicycles. (1st December 2019) - Joseph, Peter K.; Elangovan, D.; Arunkumar, G.
Highlights: Wireless power transformer exhibits a non-linear relation between the coils. A precise linear functioning region is identified in the wireless power transformer. No additional sensors required for the transformer realization in a linear region. Modeled a wireless power transmission system to design the closed-loop controller. Implemented a linear wireless charger with an efficiency of 93% at 200 mm separation. Abstract: The transportation field is witnessing a plethora of changes in vehicle electrification sector. One of the revolutionary technologies emerging in this filed is wireless power transmission. Despite various advantages like universal nature, non-physical contact and ease of access, wireless power transmission faces some limitations like flux leakage, non-linear transmitter-receiver relation, etc. This non-linear behavior of wireless power transformer causes a dynamic input-output relation throughout the operation. This leads to the use of multiple sensors which would increase the closed-loop response time. These additional sensing elements and gain determining process will reduce the power transfer efficiency in light power electric vehicles like electric bicycles. To mitigate these non-linear effects of wireless power transmission, a customized linear region is identified and implemented in this work. In this identified region of the transformer, the input-output relation will be linear, which will prevent the use of additional sensing elements. A 250 W electric bicycle is used for this study of linear control of the wireless charger. The overall efficiency of 93% is achieved for a coupling separation of 200 mm even when the primary and secondary coils have much higher misalignments. The linear closed-loop region is designed and represented with analytical equations, and the transformer efficiency obtained through these equations have been validated with the hardware outputs as well as with commercial simulations.